Access to government social programs and the tuberculosis control program: a multicenter study - Regina Célia Gollner Zeitoune (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze government social initiatives aimed at people with tuberculosis and the possibilities of access to government social programs and income transfers through the perception of tuberculosis program managers. Methods: descriptive, qualitative study with 19 managers from Belém, Recife, Campo Grande, and Rio de Janeiro, Brazil. Thematic content analysis was used. Results: there is no specific government social support for people with tuberculosis; the benefits are intended for people in social vulnerability. There are partnerships between the institutions of the secondary social healthcare network, social assistance, and community institutions. Final Considerations: the support of official bodies is important for the control of tuberculosis; however, the profile of people’s vulnerability is a determining factor for access to/destination of resources from these government social support programs.